2022
DOI: 10.1002/suco.202100452
|View full text |Cite
|
Sign up to set email alerts
|

RC members with a flexural‐strengthening layer of CFRP textile‐reinforced concrete under monotonic and cyclic long‐term loading

Abstract: Strengthening of existing reinforced concrete (RC) structures by means of externally applied fiber-reinforced polymer (FRP) reinforcement was and still is an important research topic. CFRP reinforcement is particularly suitable for infrastructure projects where the actual loads have exceeded the predictions made in the past decades and high chloride input due to deicing salts is also present. This article presents experimental and theoretical investigations on the structural behavior of RC members strengthened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Numerous studies have shown that fiber reinforced polymer (FRP), such as aramid fiber reinforced polymer (AFRP), basalt fiber reinforced polymer (BFRP), carbon fiber reinforced polymer (CFRP) and glass fiber reinforced polymer (GFRP), can significantly improve the load bearing and deformation capacity of damaged/ undamaged concrete structures. [1][2][3][4][5][6][7][8] To accurately predict the load bearing capacity of damaged concrete after FRP strengthening, many compressive strength models have been proposed. [9][10][11][12][13][14][15][16][17][18] Guo et al 19 found that a compressive strength model of FRP-confined undamaged concrete Discussion on this paper must be submitted within two months of the print publication.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that fiber reinforced polymer (FRP), such as aramid fiber reinforced polymer (AFRP), basalt fiber reinforced polymer (BFRP), carbon fiber reinforced polymer (CFRP) and glass fiber reinforced polymer (GFRP), can significantly improve the load bearing and deformation capacity of damaged/ undamaged concrete structures. [1][2][3][4][5][6][7][8] To accurately predict the load bearing capacity of damaged concrete after FRP strengthening, many compressive strength models have been proposed. [9][10][11][12][13][14][15][16][17][18] Guo et al 19 found that a compressive strength model of FRP-confined undamaged concrete Discussion on this paper must be submitted within two months of the print publication.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed an acceptable increase in flexural capacity, stiffness, ultimate bending moment, and decrease in ductility. El Ghadioui et al [76] investigated the flexural retrofitting of RB members under long-term cyclic loading. Zhang et al [77] showed that using NSM strips can achieve a 200% gain in flexural resistance.…”
Section: Beamsmentioning
confidence: 99%
“…More importantly, the FRPs are lightweight, strong, and more cost-effective components to manufacture than metal plates. Therefore, the external FRPs bonding process has been widely used to strengthen concrete beams, because it makes the material more ductile (El Ghadioui et al, 2022;Pavithra et al, 2022). Prior studies reported that the FRP composites remained elastic until brittle debonding or FRP failure occurred (Salama et al, 2019;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%